Can US Fiscal Stimulus Negatively Affect US Balance of Trade? - Adhikari, Deergha Raj; Rao, Spuma; Boudreaux, Denis (Journal of Applied Business and Economics, 2021)
In an attempt to take the U.S. economy out of recession or to stimulate a sluggish economy, US presidents, democrats and republicans alike, have used an expansionary fiscal policy. While an expansionary fiscal policy raises the GDP, it also raises a nation’s import due to increased income brought about by the expansionary fiscal policy. If the increase in a nation’s import exceeds that in export, it negatively impacts the nation’s balance of trade. So, our study examines the impact of US government stimulus spending on the nation’s balance of trade. We use a general equilibrium framework and apply the VECM model on US data from 1980 to 2020. Our study finds that, while the long-run impact of US fiscal stimulus spending on US balance of trade is positive and significant, the short-run impact is negative. We also found that any short term fluctuation in US balance of trade is adjusted to its long-run equilibrium level.